-28-11x=-8x+38

Simple and best practice solution for -28-11x=-8x+38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -28-11x=-8x+38 equation:


Simplifying
-28 + -11x = -8x + 38

Reorder the terms:
-28 + -11x = 38 + -8x

Solving
-28 + -11x = 38 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-28 + -11x + 8x = 38 + -8x + 8x

Combine like terms: -11x + 8x = -3x
-28 + -3x = 38 + -8x + 8x

Combine like terms: -8x + 8x = 0
-28 + -3x = 38 + 0
-28 + -3x = 38

Add '28' to each side of the equation.
-28 + 28 + -3x = 38 + 28

Combine like terms: -28 + 28 = 0
0 + -3x = 38 + 28
-3x = 38 + 28

Combine like terms: 38 + 28 = 66
-3x = 66

Divide each side by '-3'.
x = -22

Simplifying
x = -22

See similar equations:

| -3(x+7)+8x=4 | | 4.2d=12.18 | | -120+6x=-5x+89 | | -93-12x=-3x+105 | | 3d-80=5d+8 | | 2x^2-8-24=0 | | 1-7p=p-8p-3 | | 9+4d=2d-1 | | 9(4b-1)=2-(x+3) | | -8.3-3y-5.4-y=-3y-6.9 | | -38+2x=4x+14 | | x+(x*0.80)=810 | | 3(x+4)=9x-2(3x-6) | | 7x^2-15x+5-13x-10x^2= | | 2u^2-u+64=u^2-12u+36 | | 4-387+2x=4x+14 | | 12T-8th=-52 | | 12n6= | | 7-(4n-2)=2-5n | | 5(r-1)=20 | | 3(9+c)=2(3+c) | | 11x-8+2x-4=10x-3+2x | | 11u-6u=20 | | 12x+43=274 | | -2-36= | | 4x+10=3x+3+x-9 | | log[5](x-10)-log[5](3)=2 | | 2x^2+11x=4 | | 37x+12y=5 | | 230=-23 | | 8+2x=-7 | | f=(-16) |

Equations solver categories